Id2 exerts tumor suppressor properties in lung cancer through its effects on cancer cell invasion and migration - Chen, Jian-Ting; Hsu, Yuan-Ling; Hsu, Yi-Chiung; Tseng, Yi-Hsin; Liu, Ming-Han; Weng, Chia-Wei; Lin, Ching-Hao; Pan, Szu-Hua; Chen, Jeremy J.W.; Wang, Chi-Chung (Frontiers in Oncology, 2022)
Background: Despite advances in prognosis and treatment of lung adenocarcinoma (LADC), a notable non–small cell lung cancer subtype, patient outcomes are still unsatisfactory. New insight on novel therapeutic strategies for LADC may be gained from a more comprehensive understanding of cancer progression mechanisms. Such strategies could reduce the mortality and morbidity of patients with LADC. In our previous study, we performed cDNA microarray screening and found an inverse relationship between inhibitor of DNA binding 2 (Id2) expression levels and the invasiveness of LADC cells. Materials and Methods: To identify the functional roles of Id2 and its action mechanisms in LADC progression, we successfully established several Id2-overexpressing and Id2-silenced LADC cell clones. Subsequently, we examined in vitro the effects exerted by Id2 on cell morphology, proliferation, colony formation, invasive, and migratory activities and examined in vivo those exerted by Id2 on cell metastasis. The mechanisms underlying the action of Id2 were investigated using RNA-seq and pathway analyses. Furthermore, the correlations of Id2 with its target gene expression and clinical outcomes were calculated. Results: Our data revealed that Id2 overexpression could inhibit LADC cells’ migratory, invasive, proliferation, and colony formation capabilities. Silencing Id2 expression in LADC cells reversed the aforementioned inhibitory effects, and knockdown of Id2 increased LADC cells’ metastatic abilities in vivo. Bioinformatics analysis revealed that these effects of Id2 on cancer progression might be regulated by focal adhesion kinase (FAK) signaling and CD44/Twist expression. Furthermore, in online clinical database analysis, patients with LADC whose Id2 expression levels were high and FAK/Twist expression levels were low had superior clinical outcomes. Conclusion: Our data indicate that the Id2 gene may act as a metastasis suppressor and provide new insights into LADC progression and therapy.